Epistemologi Studi Hadis Kawasan: Konsep, Awal Kemunculan, dan Dinamika - Wendry, Novizal (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Epistemology of Area's Hadith Study: Concept, Early Emergence, and Dynamics This study focuses on the efforts of regional conceptual construction of hadith studies as a new issue in contemporary hadith science discourse. As a past event, the hadith was identically territorial. The area refers to the place where the Prophet and the narrators lived, migrated to other areas and stayed there for a long time. Uniquely, this area is included by hadith critics in their identification of the narrator after mentioning his name,Â kunyah, andÂ laqab. The data has not been written in academic form in terms genealogy as well as the developments and the changes. By using qualitative approach, in exploring the literature of early, middle and contemporary hadith sciences, this article intends to fill this void. This research found that practically the study of regional hadith had been started at the beginning of the 3rdÂ century and was done by Ahmad bin Hanbal (241 H), followed by ar-Ramahurmuzi (+360 H) and other hadith scholars. The study of regional hadith was sustained and dynamic based on regional phrases in the sub chapters and titles of hadith science literature. This study also found the phrasesÂ amá¹£Är, buldÄn, awá¹Än, marÄkiz ta`lÄ«m,Â andÂ madrasah al-hadÄ«á¹¡. The shifts of the phrases to regional hadith studies is considered as an adoption of area studies that emerged in American universities in the early twentieth century. Regional hadith studies require a multidisciplinary paradigm in order to produce novelty with a unique hadith genre in a region